Anti-CD44-Conjugated Olive Oil Liquid Nanocapsules for Targeting Pancreatic Cancer Stem Cells - Navarro-Marchal, Saúl; Griñan-Lisan, Carmen; Entrena, José Manuel; Ruiz-Alcalá, Gloria; Tristán-Manzano, María; Martín, Francisco; Pérez-Victoria, Ignacio; Peula-García, José Manuel; Marchal, Juan Antonio (ACS Publications, 2021)
The latest trends in cancer research and nanomedicine focus on using nanocarriers to target cancer stem cells (CSCs). Specifically, lipid liquid nanocapsules are usually developed as nanocarriers for lipophilic drug delivery. Here, we developed olive oil liquid NCs (O2LNCs) functionalized by covalent coupling of an anti-CD44-fluorescein isothiocyanate antibody (αCD44). First, O2LNCs are formed by a core of olive oil surrounded by a shell containing phospholipids, a nonionic surfactant, and deoxycholic acid molecules. Then, O2LNCs were coated with an αCD44 antibody (αCD44-O2LNC). The optimization of an αCD44 coating procedure, a complete physicochemical characterization, as well as clear evidence of their efficacy in vitro and in vivo were demonstrated. Our results indicate the high targeted uptake of these αCD44-O2LNCs, and the increased antitumor efficacy (up to four times) of paclitaxel-loaded-αCD44-O2LNC compared to free paclitaxel in pancreatic CSCs (PCSCs). Also, αCD44-O2LNCs were able to selectively target PCSCs in an orthotopic xenotransplant in vivo model.
Keywords: Nanopartículas; Biopolymers; Cells; Peptides and proteins; Immunology